Regional Congruence of Vegetation and Summer Climate Patterns in the Queen Elizabeth Islands, Northwest Territories, Canada - Edlund, Sylvia A.; Alt, Bea Taylor (ARCTIC, 1989)
In the Queen Elizabeth Islands, regional distributions of vegetation and many summer climate patterns show similar, distinctive S-shaped patterns, a response to the interaction between regional topography and persistent northwesterly flow from the central Arctic Ocean. The cool and cloudy central polar pack ice climate bulges almost unimpeded into the low-lying islands of the northwest and north-central sector. This region has the least vascular plant diversity and is dominated almost entirely by the herbaceous species. The mountains of Axel Heiberg and Ellesmere islands create a barrier that effectively shelters an intermontane region from both the central Arctic Ocean climate and travelling cyclonic systems. In this large intermontane zone regional minimums of cloud cover and maximums of temperatures and melt season duration are found. This area contains the most dense and diverse vascular plant assemblages. Woody species and sedges dominate, and many species with more southerly limits occur as disjuncts. The plateaus and highlands in the southern islands modify the central Arctic Ocean climate sufficiently to produce an intermediate climate. Woody species and sedges also dominate this area; however, the density and diversity are less than that of the intermontane area. Several phytogeographic limits occur in the Queen Elizabeth Islands, including the northern limits of woody plants and sedges, and the northern limits of the dominance of woody plants and sedges. These regional boundaries roughly coincide with regional mean July isotherms of 3 and 4°C respectively.Key words: Arctic, High Arctic, arctic vegetation, Canada, climate, summer climate, bioclimatic zones, Queen Elizabeth Islands, phytogeographical boundaries Mots clés: Arctique, Extrême-Arctique, végétation arctique, Canada, climat, climat estival, zones bioclimatiques, îles de la Reine-Elizabeth, limites phytogéographiques